2000
DOI: 10.1093/oxfordjournals.molbev.a026297
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Two-Component Signal Transduction

Abstract: Two-component signal transduction (TCST) systems are the principal means for coordinating responses to environmental changes in bacteria as well as some plants, fungi, protozoa, and archaea. These systems typically consist of a receptor histidine kinase, which reacts to an extracellular signal by phosphorylating a cytoplasmic response regulator, causing a change in cellular behavior. Although several model systems, including sporulation and chemotaxis, have been extensively studied, the evolutionary relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
263
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(289 citation statements)
references
References 74 publications
14
263
0
12
Order By: Relevance
“…2). Two-component system are signal transduction pathways in bacteria that respond to environmental conditions (pump is dependent on substrate) [50,73,75]. The protein AdeR (regulator) consisted of 228 amino acids is typical transcriptional regulator and protein AdeS (sensor kinase) is shorter and demonstrate activity of bacterial histidine kinase, that work together to regulate target gene expression in response to stimuli.…”
Section: Genes Of Adeabc System and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Two-component system are signal transduction pathways in bacteria that respond to environmental conditions (pump is dependent on substrate) [50,73,75]. The protein AdeR (regulator) consisted of 228 amino acids is typical transcriptional regulator and protein AdeS (sensor kinase) is shorter and demonstrate activity of bacterial histidine kinase, that work together to regulate target gene expression in response to stimuli.…”
Section: Genes Of Adeabc System and Functionmentioning
confidence: 99%
“…Phosphorilation of each domain and the transfer of phosphoryl groups between these domains is reversible by the phosphatase activity of the sensor. The histidine kinases leads to a switch between phosphorylation and dephosphorylation activities and modulates the active state of the regulators, which controls structural genes expression [9,50,138].…”
Section: Genes Of Adeabc System and Functionmentioning
confidence: 99%
“…To uncover the signal transduction routes in which these 'orphans' are involved, we compared the NJ trees (the HK and RR trees described above) of the interacting domains and coupled 'orphans' on the basis of cognate clustering within these trees. This method was successfully employed by us before (C. Francke and others, unpublished results) and it has been shown that HKs and RRs that are known to interact fall into corresponding phylogenetic subfamilies (Grebe & Stock, 1999;Koretke et al, 2000).…”
Section: Matching Of 'Orphans'mentioning
confidence: 99%
“…In fact, genes encoding TCSs are present in almost all bacteria and typically represent Յ1% of their genomes (1,2). TCSs are also present, although to a lesser extent, in archaea and eukaryotes such as fungi, slime molds, and plants (3,4). These systems are often made up of a histidine protein kinase (HPK) and a response regulator (RR).…”
mentioning
confidence: 99%